TRANS-BORDER TRAJECTORIES AND HUMAN SECURITY IN NIGERIA: NORTHEAST AND NORTHWEST IN PERSPECTIVE - JOSHUA OJI ZACHARIAH; ELIAS CHUKWUEMEKA NGWU (International Studies Journal, 2023)
The balkanization of Africa into various constituent states by the colonialists is not without obnoxious consequential effects on the continent, namely: improper border demarcation and arbitrary separation of social or ethnic groups. Similarly, the so-called delineated international borders are porous and countries exposed to various forms of human insecurity. However, successive governments have in collaboration with leaders of neighbouring countries and independently adopted different measures to checkmate irregular trans-border movements and related security disquiets but to no avail. Therefore, this article evaluates trans-border trajectories and human security in Nigeria. It particularly looks at the nexus between historical borderland nuances and food insecurity in northeast and northwest Nigeria since 2014. The paper adopted documentary method of data collection which relies on secondary sources such as journal articles, textbooks, conference and seminar papers, newspapers, etc. Analysis was done within the periscope of Lee’s migration model using content analysis method. The paper opined that poor consideration of aged-long historical ties among border communities, coupled with borderland nuances between Nigeria and neighbouring countries implicated in the rise of insecurity that has displaced and claimed the lives of thousands of people and valuable property. It further argued that trans-border related insecurity such as banditry, Boko Haram onslaughts impacted negatively on food production, availability, accessibility and stability in the study area. It thus recommends for an all-round development along with formidable modern security in every part of the country, borderland communities’ peculiarities and socio-cultural historical ties be given more meaningful consideration in every respect.